Studi Komparatif Pembentukan Portofolio Optimal Dengan Stochastic Dominance dan Single Index Model - Yuni Utami (The Indonesia Capital Market Institute, 2019)
Purpose- The study aims to see whether there is a difference between the stochastic dominance method and the single index method in forming an optimal portfolio. and seeing which method is more optimal. Methods- The sample used in the study was a real estate and property company listed on jakarta stock exchange for five years period (2013 - 2017). sampling technique in research using purposive sampling and analysis sampling techniques using average difference test (t-test). after being tested with each method both the stochastic model and the single index model, Finding- The results show that there is a difference in return from the formation of an optimal portfolio with the results of the test which results in 0.048 below the significant level of 0.05. and the results of the calculation of portfolio return formed by the stochastic method is 0.0079 smaller than the portfolio return formed by the single index method of 0.0173 which means that the single index method is more optimal than the stochastic model.